Functional characterization of two flowering repressors SHORT VEGETATIVE PHASE and TERMINAL FLOWER 1 in reblooming bearded Iris (Iris spp.). (March 2023) - Fan, Zhuping; Gao, Yike; Gao, Yaohui; Guan, Chunjing; Liu, Rong; Wang, Shiting; Zhang, Qixiang
Abstract: Reblooming bearded iris ( Iris spp.) could bloom in both spring and autumn, which has extended the ornamental periods. Our previous transcriptome analysis has indicated the possible regulatory role of SHORT VEGETATIVE PHASE ( SVP ) in reblooming of bearded iris. Moreover, it has been revealed that the mutations of TERMINAL FLOWER 1 ( TFL1 ) led to the continuous-flowering phenotypes in rose ( Rosa spp.) and strawberry ( Fragaria spp.). In order to verify the functions of these two genes on reblooming in bearded iris, IgSVP and IgTFL1 were isolated and functionally characterized. All the overexpression Arabidopsis lines of IgSVP and IgTFL1 generated the late-flowering phenotypes, indicating their functions as flowering repressors. The ectopic expression of IgSVP and IgTFL1 also generated phenotypic changes on flowers, inflorescences and branch structures. Moreover, the protein-protein interaction was found between a homologue of IgSVP and the floral meristem identity gene APETALA 1 . The expression profiling showed that IgSVP was expressed significantly lower in the rebloomers in the second floral initiation stage (T5) than those of the first one (T1) in both the once-bloomers and the rebloomers, suggesting the possible regulation of IgSVP on reblooming. However, the expression level of IgTFL1 in the rebloomers was significantly higher in T5 than that in T1. The functional characterization of the two important flowering repressors IgSVP and IgTFL1 could lay solid foundation for future molecular breeding of iris, for example, knocking out the key repressors by CRISPR/Cas9 system to extend the ornamental periods of bearded iris. Highlights: Iris spp. SHORT VEGETATIVE PHASE ( IgSVP ) and TERMINAL FLOWER 1 ( IgTFL1 ) generated late-flowering phenotypes in Arabidopsis. There is protein interaction between floral meristem identity gene Iris spp. APETALA1 and flowering repressor IgSVP. SVP may involve in the regulation of reblooming in bearded iris ( Iris spp.).